An integrated approach to mapping crustal geology and structures in the NE Capricorn Orogen, Western Australia: Implications for uranium exploration. Issue 1 (1st December 2018) - Uren, Ashley L.; Aitken, Alan R.A.; Occhipinti, Sandra A.; George, Annette D.
Abstract : Geological, geophysical and remote sensing data have been used in the northweast Capricorn Orogen to map crustal scale structures beneath Paleoproterozoic Basins that may have focused mineralising fluids. The interpretations were largely based on upwardly continued bouguer gravity and magnetic data, then tested using petrophysically constrained forward modelling techniques. The most likely interpretation for deep crustal component of the region was found to be the Bandee Seismic Provence modelled with a mafic petrophysical character. A small portion of the study area in the northern part of the study area was modelled as an extension of the Pilbara Craton with overlying Hamersley-Fortescue Groups. Various gravity lows observed in the data were tested to determine if they represented a sub-basin, granitoid intrusion or shallow batholith. The gravity lows were found to be most likely related to granitoid intrusions. One significant deep-crustal scale structure in the central-southern part of the study area can be related to a fault mapped at surface and from Landsat 8 data. The structure has had limited exploration along its extent. The integrated approached of mapping, including surface geological mapping, indicates potential carbonaceous sediments in the hangingwall of the southern major fault zone could be prospective for uranium and gold-silver mineralisation. The friable nature of the coarse grained sandstone of the Bresnahan Group, that un-conformably overlies the carbonaceous mudstone, indicates fluid flow interaction with the unconformity could have occurred which enhances the prospectivity for uranium.